Iver B. Neumann, forsvarsdebatt og fagtradisjon – kritiker, rabulist og nybrottsmann - Nina Græger (Internasjonal Politikk, 2019)
Identity, power and social structures are central topics in Iver B. Neumann’s rich authorship and contributions to Norwegian and international scholarly and political debates. This article focuses on Neumann’s contributions to the study of and discourse on Norwegian foreign, security and defence policy issues. Bringing international discourse and innovative ideas into the Norwegian setting, be they about the transformation of the armed forces in the 1990s, Norwegian NATO-membership in the early 2000s, or new theoretical perspectives within the social sciences in general and international relations in particular, Neumann has inspired engagement, indignation and important changes.